Surgical Intervention for Complicated Peptic Ulcer Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background. Peptic ulcer disease of the stomach and duodenum (DU) is one of the most common diseases, affecting 2-10% of the population in economically developed countries. Currently, drug therapy is successfully used in the treatment of peptic ulcer disease. Achievements of the late XX century brought radical changes in the understanding of the pathogenesis of peptic ulcer disease and its course, which contributed to the improvement of complex therapy with the use of powerful antisecretory and antibacterial drugs.